Plataformas computacionais de e-Science para gestão de dados científicos: estudo de caso de um programa de pesquisa da Amazônia - Silva, Ronaldo Ferreira da (2018)
Contemporary science is characterized by a large volume of data, a consequence of the growing complexity of research problems, increasingly requiring collaboration between interdiscipli-nary and inter institutional groups. In this context, the Technology of Information has been playing a relevant role in the provision of environments that enable this dynamic work. This dissertation analyzed electronic science (e-Science) platforms components available today and listed a set of indicators, involving hybrid architectures, that are able to efficiently meet the needs for scientific data management in a specific context: one research program for the Am-azon. The method used to analyze the collected data through semi-structured interviews focused on the categorization of information, by being the basis for the proposed indicators, using Con-tent Analysis techniques.